Involution and governance reform in professional football club–school integration: a case study of S City’s youth training base - Lin Wang; Chuanfang Zhu; Yuyuan Zhang; Lan Wang (Frontiers in Physiology)
The integrated development of Chinese professional football clubs and campus football has achieved good development. However, there are still many problems in terms of training methods and depth of integration. In this article, we use the involution theory (a developmental paradox where increased partnership networks fail to improve training outcomes) as an analytical perspective to explain the inner part of the case. We identify an involution dilemma in football club–school integration, characterized by overemphasis on quantitative expansion (increasing partner schools across provinces) and underinvestment in training quality (neglecting youth base development). The findings reveal a systemic “growth without development” pattern, where scaling partnerships fails to enhance talent outputs. The specific causes of the involution dilemma are stated in detail in this manuscript. Based on this, the research proposes specific corrective strategies to solve these issues.